LAYANAN BIMBINGAN KELOMPOK MELALUI TEKNIK CINEMATHERAPHY TERHADAP MINAT BELAJAR SISWA KELAS XI SMK - Marsita Dahliani Putri; Euis Eti Rohaetai; Tuti Alawiyah (IKIP Siliwangi, 2023)
This study aims to describe group guidance services through Cinema therapy techniques for students who have low self-esteem at Mts Darussalam. The research design used is descriptive qualitative research method. The subjects in the study were 5 students of class XI SMKN 2 Cimahi. Data collection methods used are interviews, documentation and observation. The data analysis used is data collection, data reduction, presentation and data conclusion drawing. The results of the research obtained from the research are group guidance services through Cinema therapy techniques carried out to students who are indicated to have low interest in learning, student responses are very good to guidance services groups through Cinema therapy techniques. Obstacles faced by BK teachers when implementing services are inadequate facilities and infrastructure. Students experience an increase in self-confidence after being provided with Cinema therapy technique group guidance services. Based on these results, group guidance services using the Cinema therapy technique can be used as a reference for further researchers who will conduct research on the level of student interest in learning. Keywords: interest in learning, group guidance, Cinematherapy